Indoor environmental quality in French dwellings and building characteristics. (March 2016) - Langer, Sarka; Ramalho, Olivier; Derbez, Mickaël; Ribéron, Jacques; Kirchner, Severine; Mandin, Corinne
Abstract: A national survey on indoor environmental quality covering 567 residences in mainland France was performed during 2003–2005. The measured parameters were temperature, relative humidity, CO2, and the indoor air pollutants: fourteen individual volatile organic compounds (VOC), four aldehydes and particulate matter PM10 and PM2.5. The measured indoor concentrations were analyzed for correlations with the building characteristics: type of dwelling, period of construction, dwelling location, type of ventilation system, building material, attached garage and retrofitting. The median night time air exchange rate (AER) for all dwellings was 0.44 h −1 . The night time AER was higher in apartments (median = 0.49 h −1 ) than in single-family houses (median = 0.41 h −1 ). Concentration of formaldehyde was approximately 30% higher in dwellings built after 1990 compared with older ones; it was higher in dwellings with mechanical ventilation and in concrete buildings. The VOC concentrations depended on the building characteristics to various extents. The sampling season influenced the majority of the indoor climate parameters and the concentrations of the air pollutants to a higher degree than the building characteristics. Multivariate linear regression models revealed that the indoor–outdoor difference in specific humidity, a proxy for number of occupants and their indoor activities, remained a significant predictor for most gaseous and particulate air pollutants. The other strong predictors were outdoor concentration, smoking, attached garage and AER (in descending order). Highlights: The indoor environment was evaluated in 567 French dwellings. Concentrations of formaldehyde was higher in newer dwellings. Season and occupancy had the strongest influence on most of the measured variables. AER had the strongest influence on aldehyde concentrations. Among building characteristics, attached garage and period of construction had the stronger effects.